2003
DOI: 10.1073/pnas.2332818100
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cu stabilizes brain superoxide dismutase 1 activity and reduces amyloid Aβ production in APP23 transgenic mice

Abstract: The Cu-binding ␤-amyloid precursor protein (APP), and the amyloid A␤ peptide have been proposed to play a role in physiological metal regulation. There is accumulating evidence of an unbalanced Cu homeostasis with a causative or diagnostic link to Alzheimer's disease. Whereas elevated Cu levels are observed in APP knockout mice, APP overexpression results in reduced Cu in transgenic mouse brain. Moreover, Cu induces a decrease in A␤ levels in APP-transfected cells in vitro. To investigate the influence of bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
255
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(277 citation statements)
references
References 46 publications
13
255
1
3
Order By: Relevance
“…The above in vivo evidence strongly suggests a beneficial effect for Cu in different AD models (18,19), indicating that Cu could be a positive player in stopping the progress of AD.…”
Section: The Pathological Role Of Copper In Alzheimer's Diseasementioning
confidence: 84%
See 1 more Smart Citation
“…The above in vivo evidence strongly suggests a beneficial effect for Cu in different AD models (18,19), indicating that Cu could be a positive player in stopping the progress of AD.…”
Section: The Pathological Role Of Copper In Alzheimer's Diseasementioning
confidence: 84%
“…They suggest that cholesterol entering the brain from the circulation of cholesterol-fed rabbits induces the neuronal accumulation Cu 1+ was monitored by the formation of a peak with maximal absorbance at 480 nm in the presence of bathocuproine disulfonic acid. More importantly, Bayer et al (18) showed that bioavailable copper is beneficial to transgenic mice over-expressing human full-length APP with the Swedish mutation (APP23 mice). Whereas aged APP23 transgenic mice showed a dramatically reduced life expectancy within the observation period, Cu-treated APP23 mice did not show this premature death phenotype.…”
Section: The Pathological Role Of Copper In Alzheimer's Diseasementioning
confidence: 99%
“…Cu 21 decreased Ab deposits in APP23 transgenic mice [Bayer et al, 2003] and Ab levels were reduced by a mutant Cu 21 transporter [Phinney et al, 2003]. Additionally, overexpression of human Ab peptides in transgenic mice decreased brain Cu 21 [Maynard et al, 2002].…”
Section: Metal Chelatorsmentioning
confidence: 92%
“…Disturbed homeostasis of these biometals in the AD brain (decreased copper levels, and increased concen--trations of iron, zinc, and manganese) has been reported (Cornett et al, 1998;Deibel et al, 1996). An imbalance of zinc and copper has been shown to significantly alter APP processing and Aβ generation in relevant animal models (Bayer et al, 2003;Borchardt et al, 1999;Phinney et al, 2003;Sparks and Schreurs, 2003;Lee et al, 2002;Friedlich et al, 2004).…”
mentioning
confidence: 98%
“…Heavy metals (e.g. lead, mercury and cadmium) are neurotoxic and associated with intellectual impairment (Bleecker et al, 2005). Recent studies have implicated lead exposure in the subsequent elevation of APP and Aβ in animals (Basha et al, 2005b) as well as in the aggregation of synthetic Aβ in vitro (Basha et al, 2005a).…”
mentioning
confidence: 99%